Uso de las redes sociales y la conducta agresiva en los estudiantes de la Unidad Educativa El Empalme, en el año 2019 - Castro Aspiazu, Luiggi Alexander (2020)
Forthedevelopment of thepresentinvestigation, thecompilation of thescientific material fromtexts, magazines and scientificarticles, as well as surveys and interviews wasconsidered, thesamedeterminedthe use of social networks, leavingtheemotionalproblemsthatitreceives as secondary. Thisproblem, being vulnerable adolescents in beingtrapped in thisworldthat leads themtodistorttheirvision of the use of social networks. Manypeoplehave a social networktoday, sincetheyhavenotyetrealizedthattheyhave fallen intosomethingaddictive, sinceit can be saidthatexcessive use causes addiction. Weworkedthrough a surveytomeasurethelevels of addiction in thepopulation. Aggressivebehavior is a set of activitypatternsthat can manifestwithvaryingintensity, from verbal and gesturalexpressionstophysicalaggression. Basedontheanalysis of theresults, itwasconcludedthat social networkshaveaffectedyoungpeople in their interpersonal relationships; This is because verbal communication has diminished and is carriedoutthroughthese social networks; Likewise, his academic performance has beenaffected.